The pediatric surgery workforce in low- and middle-income countries: problems and priorities - Krishnaswami, Sanjay; Nwomeh, Benedict C.; Ameh, Emmanuel A. (Seminars in pediatric surgery, 2016)
Most of the world is in a surgical workforce crisis. While a lack of human resources is only one component of the myriad issues affecting surgical care in resource-poor regions, it is arguably the most consequential. This article examines the current state of the pediatric surgical workforce in low- and middle-income countries (LMICs) and the reasons for the current shortfalls. We also note progress that has been made in capacity building and discuss priorities going forward. The existing literature on this subject has naturally focused on regions with the greatest workforce needs, particularly sub-Saharan Africa (SSA). However, wherever possible we have included workforce data and related literature from LMICs worldwide. The pediatric surgeon is of course critically dependent on multi-disciplinary teams. Surgeons in high-income countries (HICs) often take for granted the ready availability of excellent anesthesia providers, surgically trained nurses, radiologists, pathologists, and neonatologists among many others. While the need exists to examine all of these disciplines and their contribution to the delivery of surgical services for children in LMICs, for the purposes of this review, we will focus primarily on the role of the pediatric surgeon.